Determinants Of The Resilience Of Mothers Who Have Down Syndrome Children - Kuzzairi, Kuzzairi; Taufiqurrahman, Taufiqurrahman; Susilawati, Endang Fauziyah (Poltekkes Kemenkes Yogyakarta, 2023)
This study, conducted at the Surabaya POTADS Foundation, aims to identify the determinants of resilience in mothers with children who have Down syndrome. Acknowledging the unique challenges posed by raising a child with Down syndrome, this research focuses on the mother's resilience, given their often close relationship with the child. The study employed an analytical observational design with a cross-sectional approach, using questionnaires as the primary data collection tool. Ten mothers, selected through purposive sampling, participated in the study. The variables examined included individual factors, family factors, community factors, risk factors, and resilience. The data were analyzed using logistic regression statistical tests. The simultaneous test (F test) revealed that the combined independent variables (individual, family, community, and risk) do not significantly affect the resilience of the mothers (F calculated = 2.930 < F table 4.53, Sig = 0.135 > 0.05), leading to the rejection of the hypothesis (H_1). Similarly, the partial test (T test) indicated that none of these independent variables individually exert a significant impact on resilience, with all p-values exceeding 0.05. This lack of influence was attributed to factors such as low cognitive function, inadequate coping strategies, low locus of control, negative self-concept, absence of family support, and low social skills. The study highlights the complex interplay of various factors in shaping resilience among mothers of children with Down syndrome.